Multiresonant Fiber Acoustic Sensors with Stabilized Triple-Phase Demodulation for Large Dynamic Ranges - Xingyu Wei; Jinda Du; Junfeng Zhou; Xinlu Deng; Zhiran Yi; Lei Shao; Wenming Zhang (Advanced Devices & Instrumentation)
Extrinsic fiber acoustic sensors have gained marked attention for their potential in remarkable sensitivity and minimum detectable pressure (MDP), together with advantages of immunity to polarization fading. Their extreme sensitivity, however, leads to excessive drifts that bring substantial 1/f noise and complicate the demodulation process. Here, we present a stabilized triple-phase demodulation architecture that effectively suppresses 1/f noise and ensures a nondrifting phase output with a low, flat noise floor of 173 μrad/[Formula: see text] without any prior calibration. We also propose a labyrinth-inspired multiresonant membrane for wide-bandwidth sound capture. As a result, an outstanding linear dynamic range of 115.72 dB and wideband acoustic spectrum coverage from 20 Hz to 15 kHz are achieved. Our sensor also displays a high sensitivity of 1.02 rad/Pa (−119.83 dB ref: 1 rad/μPa) and an MDP of 81.84 μPa/[Formula: see text] at its first resonance. We demonstrate exceptional sound detection capabilities across a large dynamic range of pressures, such as ecosystem perception, speech recognition, and shock detection. These findings highlight our sensor’s potential in diverse voice interaction and hyper-alert acoustic sensing.